2020
DOI: 10.1016/j.jcat.2020.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Rapid scan FTIR reveals propane (am)oxidation mechanisms over vanadium based catalysts

Abstract: Rapid scan FTIR coupled with Mass Spectrometry (MS) has been used to determine the role of spectroscopically observed species in the reaction media during propane dehydrogenation over a V/Al catalyst, and propane ammoxidation on a Sb-V-O sample. During the propane dehydrogenation reaction, it was shown that oxygenates are not formed during the first minutes and propylene is formed directly from propane via dehydrogenation on a V-O site. Oxygenates may form though secondary reactions due to further propylene ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…The bands at 2919 and 2974 cm −1 in Figure 7c could be ascribed to C 3 H 8 adsorption. 36 When light was introduced, 2919 and 2974 cm −1 bands disappeared quickly. It demonstrates the fast conversion of the adsorbed C 3 H 8 .…”
Section: Positive Effect Of Photon Injection On Activitymentioning
confidence: 99%
“…The bands at 2919 and 2974 cm −1 in Figure 7c could be ascribed to C 3 H 8 adsorption. 36 When light was introduced, 2919 and 2974 cm −1 bands disappeared quickly. It demonstrates the fast conversion of the adsorbed C 3 H 8 .…”
Section: Positive Effect Of Photon Injection On Activitymentioning
confidence: 99%
“…Guerrero-Pérez et al used a rapid-scan FTIR equipped with a mass spectrometer to elucidate the mechanism of propane ammoxidation and oxidation reactions. 66 They found that the oxygenates were not formed at the outset of the reaction. They stated that propylene promptly evolved from propane, and oxygenates may be produced by the subsequent reactions (e.g., propylene ammoxidation to AN).…”
Section: Perspectivementioning
confidence: 99%